2022
DOI: 10.1155/2022/1127095
|View full text |Cite|
|
Sign up to set email alerts
|

Computational Analysis of the Related Factors of Deep Vein Thrombosis (DVT) Formation in Patients Undergoing Hip Fracture Surgery

Abstract: A retrospective study was conducted on 51 patients undergoing hip fracture surgery to investigate the factors associated with the formation of deep venous thrombosis (DVT). The independent sample t-test and correlation analysis were used to sort out and analyze the data. The findings are as follows. (1) Different gender samples showed significant differences in the Caprini score and thrombus location. Most DVTs in females are located in the posterior tibial vein and intermuscular veins. The Caprini score of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This is the first retrospective study on the association between admission MCV and preoperative DVT in geriatrics with hip fractures. Previous studies suggested age, sex, hyperlipidemia, dementia, movement disorder, bedridden time, diabetes, pulmonary disease, d-dimer, and kidney disease as risk factors for developing DVT after fractures [ 9 , 21 24 ]. Meantime, many studies have found that laboratory indicators of blood routine, such as RDW (red cell distribution width), blood monocyte count, and hematocrit, were risk factors for postoperative deep vein thrombosis in patients with hip fracture [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first retrospective study on the association between admission MCV and preoperative DVT in geriatrics with hip fractures. Previous studies suggested age, sex, hyperlipidemia, dementia, movement disorder, bedridden time, diabetes, pulmonary disease, d-dimer, and kidney disease as risk factors for developing DVT after fractures [ 9 , 21 24 ]. Meantime, many studies have found that laboratory indicators of blood routine, such as RDW (red cell distribution width), blood monocyte count, and hematocrit, were risk factors for postoperative deep vein thrombosis in patients with hip fracture [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is observed a significant increase in DVT incidence in the control group compared with the treatment group (p < 0.05) (Table II). Currently, the main clinical prevention methods for DVT are anticoagulant drugs and early functional exercise [21][22][23]. LMWH is one of the most used anticoagulant drugs in clinical practice, which not only stimulates the release of plasminogen activator from vascular endothelium, but also accelerates fibrinolysis to reduce the agglutination of red blood cells as well as PLT in the blood [24].…”
Section: Dvt Incidence Evaluationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%